Guía para la elaboración de material didáctico para la enseñanza-aprendizaje en el Área de Ciencias Naturales, aplicada para el cuarto y quinto años de educación básica de la Escuela "Julio María Matovelle", El Quinche. - Conejo Morales, Marcia Gladys (2014)
Longtime education has been considered a school system iterative learning in the rural sector, whether for economic and social reasons of both the teacher and student and the process of the advancement in technology that generates the need to provide quality the education of our children. These elements make it possible for new entrepreneurial ideas based on innovative strategies that result in improved student engagement and therefore better training of teachers generated. The results obtained in the evaluation of school learning Julio María Matovelle in the area of Natural Sciences, fourth and fifth years of basic education, they note the low levels of learning because of all students who are enrolled in the fourth and fifth year, have low achievement in this area, lack of teaching resources to deepen topics.